The Role of Parents in Online Learning Motivation for Sixth-Grade Elementary School Students - Sulistya Nurul Fikriah; Diki Rukmana (Universitas Muhammadiyah Surakarta, 2022)
This research sought to determine how parental roles affected children's motivation for online learning during the COVID-19 pandemic. This study employed a quantitative correlational survey as its methodology. The questionnaire was used to collect data for this study. While SEM-PLS (Structural Equation Modeling-Partial Least Square) analysis is used to test hypotheses, CFA (Confirmatory Factor Analysis) is used to assess validity and reliability. SmartPLS 3.0 software is used to assist in all data processing. The factor analysis results indicated a sufficient correlation between the 30 items of the instruments used to support the structure of each variable. According to the results of the SEM analysis, parents significantly impact their children's desire to learn online at home when it comes to the online learning system utilized by elementary school students. Four indicators measure parents' performance: providing guidance (PG), learning facilities (LF), rewards and praise (RP), and attention and supervision (AS) (AS). The results of this study indicate that parental roles (LF, PG, and RP) affect learning motivation, as indicated by P-values of (0.000 0.05), (0.035 0.05), and (0.006 0.05), respectively. In contrast, US indicators have no effect on parental roles and learning motivation, as indicated by the P-value of (0.879 0.05 In order to improve the home education system while still leaving a positive impression on children, parents' roles must become more child-centered. Due to their rigorous nature, the instrument validity techniques of CFA and the data analysis techniques of SEM enhance the validity and reliability of research findings